Quorum Sensing and the Use of Quorum Quenchers as Natural Biocides to Inhibit Sulfate-Reducing Bacteria - Giantommaso Scarascia; Tiannyu Wang; Pei-Ying Hong (Antibiotics, 2016)
Sulfate-reducing bacteria (SRB) are one of the main protagonist groups of biocorrosion in the seawater environment. Given their principal role in biocorrosion, it remains a crucial task to develop strategies to reduce the abundance of SRBs. Conventional approaches include the use of biocides and antibiotics, which can impose health, safety, and environmental concerns. This review examines an alternative approach to this problem. This is achieved by reviewing the role of quorum sensing (QS) in SRB populations and its impact on the biofilm formation process. Genome databases of SRBs are mined to look for putative QS systems and homologous protein sequences representative of autoinducer receptors or synthases. Subsequently, this review puts forward the potential use of quorum quenchers as natural biocides against SRBs and outlines the potential strategies for the implementation of this approach.